The Representation of Higher Education on the Advertisement Billboards of Private Universities in Yogyakarta - Irene Santika Vidiadari (Universitas Muhammadiyah Ponorogo, 2021)
The competition to get students has made universities promote themselves intensively. One of the promotional media they use is the billboard, outdoor media placed at strategic locations. This paper discusses the discourse of education on the billboard advertisement of private universities in Yogyakarta using Gunther Kress and Theo van Leuween’s multimodal analysis. The result shows that the university is put forward as an institution that prepares students before entering working life as pictured through the visual and linguistic messages, e.g., the illustration of study success, explanation concerning job opportunities, institutional achievement, and inter-institutional collaboration as indicated through the images of physical and human resource development. In terms of promotion, the discourse of education appears through constructing reputation, prospect, and educational product variants.